2008
DOI: 10.1002/macp.200700448
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(N‐aryl‐2,7‐carbazole)s for Efficient Blue Electroluminescence Materials

Abstract: Several poly(N‐phenyl‐2,7‐carbazole)s that have dialkoxy groups at the m‐ and p‐positions (PmpCzDC, PmpPhDC, PmpCBiDC, PmpEHC), a silyl group at the p‐position (PpPhDSiC), and a diphenylamino group (PmPhDAC, PmEHAC) at the m‐position of the N‐phenyl portion are synthesized, and their optical properties are characterized. These polymers have been used as emitting layer materials of organic light‐emitting diode (OLED) devices that have a configuration of ITO/PEDOT(PSS)/polymer/CsF/Al. The OLED devices embedded w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 30 publications
1
50
0
Order By: Relevance
“…Poly(carbazole‐2,7‐diyl)s are one of the blue light‐emitting materials first reported in 2001 6. In these years, we have demonstrated that poly( N ‐arylcarbazole‐2,7‐diyl)s have good solubility in organic solvents, quantitative fluorescence quantum efficiency, good EL performance with higher luminance than 10,000 cd m −2 and maximum efficiency over 2.0 cd A −1 , and these EL results were superior to polyfluorenes and poly( N ‐alkylcarbazol‐2,7‐diyl)s 4,7. Generally, polycarbazoles have good hole‐injection ability8 and at the same time electron injection ability is low, which means balancing of carriers' injection into the emitting layer of polycarbazoles is difficult during PLED operations.…”
Section: Introductionmentioning
confidence: 92%
“…Poly(carbazole‐2,7‐diyl)s are one of the blue light‐emitting materials first reported in 2001 6. In these years, we have demonstrated that poly( N ‐arylcarbazole‐2,7‐diyl)s have good solubility in organic solvents, quantitative fluorescence quantum efficiency, good EL performance with higher luminance than 10,000 cd m −2 and maximum efficiency over 2.0 cd A −1 , and these EL results were superior to polyfluorenes and poly( N ‐alkylcarbazol‐2,7‐diyl)s 4,7. Generally, polycarbazoles have good hole‐injection ability8 and at the same time electron injection ability is low, which means balancing of carriers' injection into the emitting layer of polycarbazoles is difficult during PLED operations.…”
Section: Introductionmentioning
confidence: 92%
“…The strategy used to improve the electroluminescence properties was the modification of the substituents on the nitrogen atom. A wide variety of alkyl chains [76,90] and aryl groups [95,96,[105][106][107] have been tested to obtain highly performing materials. Recently, a new carbazole monomer bearing a sulfonate group at the end of the alkyl chain was synthesized [108].…”
Section: Poly(27-carbazole)s For Light-emitting Diodesmentioning
confidence: 99%
“…Matthias Rehahn et al [8] Synthesis of Poly(N-aryl-2,7-carbazole)s for Efficient Blue Electroluminescence Materials Masashi Kijima et al [9] Conductive Polymer Electrolytes Derived from Poly(norbornene)s with Pendant Ionic Imidazolium…”
Section: Approachesmentioning
confidence: 99%